Comparative investigation of mechanical and cooling performance between thermochromic road materials prepared by wet/dry process: For low-carbon production and sustainable service. (1st August 2022) - Chen, Zihao; Liu, Jianxin; Zhang, Henglong; Kuang, Huaping; Zhao, Mengting; Zhang, Shuai
Abstract: The thermochromic road materials are developed as an emerging type of cool pavement material to alleviate the urban heat island effect. Different preparation methods with regard to thermochromic road materials not only influence the serviceability of product itself but also induce disparities in energy consumption, waste emission and the environment impact during production process. The objective of this research is to investigate the effects of different preparation methods (including wet process and three dry processes with different mixing sequences) on mechanical and cooling performance for low-carbon production and sustainable service of thermochromic road materials. The mechanical performance including Marshall mechanical stability, low-temperature cracking resistance, moisture susceptibility and permanent deformation were evaluated. Further, the mechanical performance differences caused by different preparation methods were assessed through analysis of variance (ANOVA). The temperatures inside different asphalt mixtures that were exposed to solar radiation in hot summertime were monitored for cooling performance evaluation. Additionally, the mechanism behind the cooling performance disparities was revealed by analyzing the integrity and distribution characteristic of thermochromic microcapsules inside asphalt mixtures. The results indicate that the thermochromic microcapsule modified asphalt mixture prepared by wet process shows better mechanical performance than those prepared by dry process in general. The different process characteristics between wet and dry method, as well as different mixing orders in dry process, can cause significant effects on some mechanical performance of thermochromic microcapsule modified asphalt mixture. The wet process contributes to a more uniform distribution of thermochromic microcapsules inside mixtures while the dry process is more beneficial to preserving the integrity of thermochromic microcapsules. Based on superposition of two aspects about integrity and distribution, the wet process allows thermochromic road materials to show a better cooling effect in comparison with dry process. Highlights: The wet process contributes to a better cooling effect compared with dry process. The high-temperature stability of pavement is largely improved by cooling effect. Cooling effect is related to integrity and distribution of microcapsule in mixture.